2015
DOI: 10.1152/ajpgi.00256.2015
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinase 9-induced increase in intestinal epithelial tight junction permeability contributes to the severity of experimental DSS colitis

Abstract: Nighot P, Al-Sadi R, Rawat M, Guo S, Watterson DM, Ma T. Matrix metalloproteinase 9-induced increase in intestinal epithelial tight junction permeability contributes to the severity of experimental DSS colitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
93
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(96 citation statements)
references
References 65 publications
(72 reference statements)
2
93
0
1
Order By: Relevance
“…In this context, expression of MMP9 was found to be increased in IBD, particularly in patients with ulcerative colitis 74 . Functional data in experimental models of inflammation have suggested an important role of MMP9 in impairing colonic epi thelial permeability and augmenting inflammation via activation of myosin light chain kinase (MLCK) 74 .…”
Section: Emerging Targets In Fibrosis and Tissue Remodellingmentioning
confidence: 91%
See 1 more Smart Citation
“…In this context, expression of MMP9 was found to be increased in IBD, particularly in patients with ulcerative colitis 74 . Functional data in experimental models of inflammation have suggested an important role of MMP9 in impairing colonic epi thelial permeability and augmenting inflammation via activation of myosin light chain kinase (MLCK) 74 .…”
Section: Emerging Targets In Fibrosis and Tissue Remodellingmentioning
confidence: 91%
“…In this context, expression of MMP9 was found to be increased in IBD, particularly in patients with ulcerative colitis 74 . Functional data in experimental models of inflammation have suggested an important role of MMP9 in impairing colonic epi thelial permeability and augmenting inflammation via activation of myosin light chain kinase (MLCK) 74 . Furthermore, MMP9 favoured angiogenesis and created a proteolytic environment in the inflamed gut of a mouse model of colitis that stimulated the influx of myeloid cells into the colonic epithelium and the prod uction of TNF 75,76 .…”
Section: Emerging Targets In Fibrosis and Tissue Remodellingmentioning
confidence: 91%
“…Previous studies from our laboratory and other groups have also demonstrated a central role of MLCK in modulating intestinal TJ barrier function or intestinal permeability [30,31,4446]. These studies indicated that an increase in MLCK expression leads to MLCK-catalyzed phosphorylation of myosin light chain, contraction of peri-junctional actin/ myosin filaments, and contractile tension-generated mechanical opening of the TJ barrier and an increase in intestinal permeability [31].…”
Section: Discussionmentioning
confidence: 83%
“…In MMP-9 knock-out mice, DSS-induced colitis and the associated increase of intestinal permeability are attenuated [93]. Accordingly, selective inhibition of MMP-9 reduces disease severity in mice [94].…”
Section: Role Of Neutrophil-derived Moleculesmentioning
confidence: 99%